2022
DOI: 10.7554/elife.79278
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variants of sphingomyelin synthase SMS2 disrupt lipid landscapes in the secretory pathway

Abstract: Sphingomyelin is a dominant sphingolipid in mammalian cells. Its production in the trans-Golgi traps cholesterol synthesized in the ER to promote formation of a sphingomyelin/sterol gradient along the secretory pathway. This gradient marks a fundamental transition in physical membrane properties that help specify organelle identify and function. We previously identified mutations in sphingomyelin synthase SMS2 that cause osteoporosis and skeletal dysplasia. Here we show that SMS2 variants linked to the most se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Our lipidomic data are fully consistent with a gradual increase of lipid saturation along the secretory pathway (Van Meer et al, 2008 ; Bigay and Antonny, 2012 ), thereby complementing previous work on the composition of the trans-Golgi network/endosomal (TGN/E) system, secretory vesicles, and the plasma membrane in yeast (Klemm et al, 2009 ; Surma et al, 2011 ). Likewise, the ergosterol level of 9.7 mol% in the yeast ER membrane is consistent with previous estimations (Zinser and Daum, 1995 ; Schneiter et al, 1999 ; Van Meer et al, 2008 ) and parallels findings in mammalian cells, for which a resting cholesterol level in the ER between 7 and 8 mol% has been reported along with a switch-like regulation of sterol response element binding protein (SREBP) processing, when the level of cholesterol drops below 5 mol% in the ER (Radhakrishnan et al, 2008 ; Sokoya et al, 2022 ). From a cell biological viewpoint, our data suggest that the sterol gradient along the secretory pathway is rather flat from the ER (9.7 mol%) to the TGN/E system (9.8 mol%) (Klemm et al, 2009 ).…”
Section: Discussionsupporting
confidence: 87%
“…Our lipidomic data are fully consistent with a gradual increase of lipid saturation along the secretory pathway (Van Meer et al, 2008 ; Bigay and Antonny, 2012 ), thereby complementing previous work on the composition of the trans-Golgi network/endosomal (TGN/E) system, secretory vesicles, and the plasma membrane in yeast (Klemm et al, 2009 ; Surma et al, 2011 ). Likewise, the ergosterol level of 9.7 mol% in the yeast ER membrane is consistent with previous estimations (Zinser and Daum, 1995 ; Schneiter et al, 1999 ; Van Meer et al, 2008 ) and parallels findings in mammalian cells, for which a resting cholesterol level in the ER between 7 and 8 mol% has been reported along with a switch-like regulation of sterol response element binding protein (SREBP) processing, when the level of cholesterol drops below 5 mol% in the ER (Radhakrishnan et al, 2008 ; Sokoya et al, 2022 ). From a cell biological viewpoint, our data suggest that the sterol gradient along the secretory pathway is rather flat from the ER (9.7 mol%) to the TGN/E system (9.8 mol%) (Klemm et al, 2009 ).…”
Section: Discussionsupporting
confidence: 87%
“…Variants p.Ile62Ser and p.Met64Arg do not have an effect on SMS2 enzymatic activity. Instead, due to the missense variants, SMS2 is unable to exit the ER because their N-terminal cytosolic tails lack a functioning independent ER export signal ( 31 ). Sokoya et al.…”
Section: Enzymatic Activity and Cellular Location Of The Sms2 Variantsmentioning
confidence: 99%
“…demonstrated that isoleucine at position 62 and methionine at position 64 in SMS2 are part of a conserved sequence motif, IXMP, which is located 13–14 residues upstream of the first membrane span and is part of this ER export signal ( Figure 2 ). By transfecting SMS2 I62S and SMS2 M64R constructs into Hela cells, they detected the subcellular location of the SMS2 variants with immunofluorescence microscopy, and revealed that SMS2 I62S and SMS2 M64R were both retained in the ER, while wild type SMS2 localized to the Golgi and the plasma membrane ( 31 ). The SMS2 p.Arg50* variant is predicted to result in a truncated enzyme lacking the entire transmembrane helices including the active sites of the enzyme ( Figure 2 ) ( 4 ).…”
Section: Enzymatic Activity and Cellular Location Of The Sms2 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids are a structurally diverse class of lipids with properties essential for the evolution of eukaryotic cells. They typically represent ∼ 15% of cellular lipids and are highly enriched in the plasma membrane (PM) where they modulate key physical membrane properties, including fluidity, thickness, and curvature (1,2).…”
Section: Introductionmentioning
confidence: 99%